2000
DOI: 10.1177/003329410008700201
|View full text |Cite
|
Sign up to set email alerts
|

An Ethnocultural Study of Posttraumatic Stress Disorder in African-American and White American Vietnam War Veterans

Abstract: This study examined the intensity of Posttraumatic Stress Disorder (PTSD) symptoms as measured by the Mississippi Scale, the Keane (PK), and the PTSD (PS) Scales of the MMPI-2 in a sample of 34 African-American and 34 White American Vietnam War Veterans who sought treatment in a Specialized Inpatient PTSD Unit. The scores of the two groups on the Beck Depression Inventory and the clinical scales of the MMPI-2 were also compared. The ethnoculturally different sample was matched on intensity of combat exposure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…On balance, few meaningful differences were found in this sample between African American and Caucasian combat veterans with PTSD. As expected, the findings of this study replicated clinical symptom pattern findings of previous studies (e.g., Frueh et al, 1997; Monnier et al, 2002; Trent et al, 2000) indicating that African Americans and Caucasians do not differ on demographic variables, comorbid psychiatric disorders, or measures of anxiety, depression, or PTSD symptomatology. The groups also did not differ on most measures of dissociation, paranoia, or psychosis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On balance, few meaningful differences were found in this sample between African American and Caucasian combat veterans with PTSD. As expected, the findings of this study replicated clinical symptom pattern findings of previous studies (e.g., Frueh et al, 1997; Monnier et al, 2002; Trent et al, 2000) indicating that African Americans and Caucasians do not differ on demographic variables, comorbid psychiatric disorders, or measures of anxiety, depression, or PTSD symptomatology. The groups also did not differ on most measures of dissociation, paranoia, or psychosis.…”
Section: Discussionsupporting
confidence: 89%
“…A number of studies have looked for racial differences among combat veterans with PTSD on clinical symptom patterns by using standardized psychometric instruments (e.g., Minnesota Multiphasic Personality Inventory–2; MMPI-2), psychiatric interviews, or retrospective chart review (Frueh, Brady, & de Arellano, 1998). Some authors reported broad differences in the manifestation of symptoms across general measures of psychopathology (Penk, Robinowitz, Dorsett, Bell, & Black, 1988), others found only small but circumscribed differences on measures of psychotic or dissociative symptomatology (e.g., Frueh et al, 2002; Frueh, Smith, & Libet, 1996), although most others have failed to find any significant racial differences across relevant variables (e.g., Keane & Wolfe, 1990; Frueh, Gold, de Arellano, & Brady, 1997; Monnier, Elhai, Frueh, Sauvageot, & Magruder, 2002; Trent, Rushlau, Munley, Bloem, & Driesenga, 2000).…”
Section: Epidemiology and Clinical Manifestationmentioning
confidence: 99%
“…However, there are mixed findings regarding the comparability of mean scores on the BDI between African Americans and European Americans. Whereas some studies have found comparable mean BDI scores (e.g., Lester & DeSimone, 1995;Trent, Rushlau, Munley, Bloem, &. Driesenga, 2000), others have reported higher scores among African Americans (e.g., Cavanaugh, 1983).…”
Section: The Bdi and Bdi-ii African Americansmentioning
confidence: 97%